1989 Atlantic Universities Geological Conference: November 2-4, 1989

(untitled) (Atlantic Geoscience Society, 1989)
Beginning this year, the abstracts of the annual Atlantic Universities Geological Conference will be published in "Atlantic Geology." This will provide a permanent record of the abstracts, and also focus attention on the excellent quality of and interesting and varied science in these presentations. The Editors